Access to Credit as a Growth Constraint - Matjaž Volk; Polona Trefalt (Journal of Banking and Financial Economics)
From a sample of 75,854 Slovenian fi rms in the period 1995–2011, we examine the effects of a fi rm’s access to bank credit on its growth. The results suggest that as the external fi nancing constraint relaxes and fi rm gets access to credit, the reliance on internal funds to fi nance growth decreases. By exploring the role of available collateral in gaining access to bank credit, we find that collateral only helps larger fi rms to obtain credit more easily. On the other hand, collateral does not reduce micro fi rms’ dependence on internal funds to fi nance growth, which suggests that even if they have collateral, banks are still unprepared to finance them, possibly due to the level of risk. It could also be that in approving credit to micro firms, other factors such as liquidity or cash fl ow are more highly considered by banks than the value of collateral.